Pengaruh Permainan Scrabble Terhadap Peningkatan Penguasaan Kosakata dan Spelling Bahasa Inggris pada Siswa Sekolah Dasar - Muhammad Ikhwanurrahim; Yunida Tria Ningsih (STIKes Ibnu Sina Ajibarang, 2025)
This research was conducted based on the recognition of vocabulary mastery as a fundamental aspect of English language proficiency, particularly at the elementary school level, where vocabulary serves as the basis for developing other language skills such as speaking, reading, listening, and writing. In addition, the study was also motivated by the need for innovative, creative, and interactive learning media to foster students’ engagement and interest in learning English. The objective of this research was to examine the effectiveness of Scrabble, a word-based educational game, in enhancing students’ vocabulary mastery. The research applied an experimental method with a quasi-experimental design, specifically the pretest–posttest nonequivalent control group design. A total of 20 elementary school students were involved and divided into two groups: an experimental group and a control group. The experimental group was taught using Scrabble as a learning medium, while the control group was taught using conventional teaching methods. Data on students’ vocabulary mastery were collected through pretests and posttests and analyzed using statistical comparisons to determine the significance of the improvements. The findings revealed a substantial improvement in the experimental group, whose average score increased from 13.20 in the pretest to 57.75 in the posttest, representing a gain of 44.55 points. In contrast, the control group showed only a modest improvement, rising from 12.54 to 33.99, with an overall gain of 21.45 points. These results clearly indicate that Scrabble-based learning is significantly more effective than traditional methods in improving vocabulary acquisition and spelling accuracy. The implications of this study emphasize the potential of Scrabble as an innovative and enjoyable learning medium that can actively involve students in the learning process, encourage collaboration, and improve language proficiency.